MEDIASI PERAN ORANG TUA DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA MASA PANDEMI COVID-19 - Ardiansyah, Ardiansyah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study was to examine the effect of mediating the role of parents and students' learning motivation on student achievement during the Covid-19 pandemic.The research method in this study used a quantitative approach with field studies andconfirmatory methods. Data analysis was carried out using the Structural EquationModeling (SEM) approach with the Partial Least Square technique. The software toolsused are Smart PLS 3.3.2. The research was conducted at SMA Negeri 02 Gorontalo with the number of research respondents 51 students with saturated sampling techniqueThe results of this study are (1) learning motivation has a positive and significant effect on learning achievement with a significance value of 0.000 and t-count t-table (4.589  2.010), (2) learning motivation has a positive and significant influence on the role of people. parents with a significance value of 0.000 and t-count t-table (8.975 2.010), (3) the role of parents has a positive and significant influence on learning achievement with a significance value of 0.001 and t-count t-table (3,405 2.010), (4) and the role of parents can mediate the effect of the relationship of learning motivation on student learning achievement with a significance value of 0.006 and t-count t-table (2.784  2.010). Learning achievement can be influenced by learning motivation and the role of parents either directly or indirectly.